Pemberdayaan pengelolaan desa wisata berkelanjutan di Desa Tanjung Lanjut Kecamatan Sekernan Kabupaten Muaro Jambi - Firmansyah Putra; Saidina Usman; M Yusuf (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Tanjung Lanjut Village Sekernan sub-district of Muaro Jambi region has Tangkas lake as potential of beautiful tourism. The lake has a unique attraction with the Putat tree flowering red Flanconia Valida which blooms and falls around July to August in every year. The potential of tourist attractions in this village managed by Village-Owned Enterprises but has not sustainable and has not an impact on increasing income for the local community. Based on the problems above, the solution implemented in the community service activities is the assistance of the of tourism and promotion. This empowering activity is carried out by 1). Transfer of knowledge of sustainable management (economic, social, and environmental aspects). 2) Training and capacity building assistance. Based on the results of service activities, there was an increase in knowledge, motivation, managerial ability, and technical skills in managing sustainable tourism potential, which had an impact on increasing the number of visitors. Impact the increasing of the visitors contribute new economic resources or alternatives for local people who have only relied on the plantation and agriculture sectors. Other findings indicate that the management of Tangkas Lake did not have sufficient cooperation and networking capabilities with various levels of partners. Thus further assistance is needed in enhancing collaboration and networking skills.